Editorial - Fernández-Arata, Manuel (2019)
The original articles section begins with the study conducted by Joel Seminario-Quiñones, Juan Walter Pomahuacre Carhuayal, Yuri Chávez, Heber Gómez, Roxana Portocarrero, Giuliana Gamero-Vega, Ada Calderón-Giraldo, Elizabeth López, Martín Castro and Juan Carlos Bazo-Álvarez on the psychometric properties of the Inventory of Study Habits CASM-85 in high school students from four Peruvian cities. It concludes that the CASM-85 short form (45 items) has shown better psychometric properties than its original full form. Second, Gina Pamela Pancorbo Valdivia, Mathias Schmitz, Ian Nightingale Ferrer, Andrés Manuel Palacios Agurto and Agustín Espinosa report on a study that examines stereotypical representations and prejudice towards different Peruvian social groups by high-socioeconomic-status group members from Lima, who identify and value White Peruvians as a high-status group, competent and developed but also corrupt. At the same time, they identify and value Amazonian and African Peruvians to a lesser extent, who are considered as low-status, underdeveloped but joyful groups. Third, authors María Antonella Gilla and Silvina Belén Giménez present the adaptation and validation of the Maslach Burnout Inventory - Human Services Survey (MBI-HSS) in mental health professionals. They conclude that it is a valid and reliable scale to evaluate Argentinian psychiatrists and psychologists. Fourth, Juan Jiménez Flores, Luz María Flores Herrera and César Merino Soto evaluate a model of family risk factors and harsh discipline practices that predicts child’s aggressive behavior. They conclude that maternal anxiety and marital violence have significant effects on child’s aggressive behavior, which is mediated by disciplinary practices. Fifth, Mariano Castellaro and Nestor Roselli analyze the effects of competence symmetry-asymmetry and socio-affective affinity on the collaborative interaction, finding a distinguishing effect of socio-affective affinity on cognitive symmetry, where it is associated with a lower imbalance of peers’ contributions related to the resolution of the task. Meanwhile, in competition symmetry, the influence of the socio-affective affinity was minimal...